2021
DOI: 10.1371/journal.pone.0250675
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacterial communities across 12 Ensifera (Orthoptera) at different feeding habits and its prediction for the insect with contrasting feeding habits

Abstract: Insect microbial symbioses play a critical role in insect lifecycle, and insect gut microbiome could be influenced by many factors. Studies have shown that host diet and taxonomy have a strong influence on insect gut microbial community. In this study, we performed sequencing of V3-V4 region of 16S rRNA gene to compare the composition and diversity of 12 Ensifera from 6 provinces of China. Moreover, the influences of feeding habits and taxonomic status of insects on their gut bacterial community were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
4
14
0
Order By: Relevance
“…Cyanobacteria was the fourth dominant phyla in the FAW gut across the three diets used in this study. This result is in line with the studies by Zheng et al (2021) who reported that Cyanobacteria was the third dominant phyla in the gut of Ensifera (Orthoptera) with different feeding habits and the second dominant phyla in herbivorous Ensifera. Contrarily, Cyanobacteria were found in very low abundance in reared Henosepilachna vigintioctopunctata (Coleoptera) (Lü et al, 2019) and in wild and mass-reared…”
Section: Discussionsupporting
confidence: 93%
“…Cyanobacteria was the fourth dominant phyla in the FAW gut across the three diets used in this study. This result is in line with the studies by Zheng et al (2021) who reported that Cyanobacteria was the third dominant phyla in the gut of Ensifera (Orthoptera) with different feeding habits and the second dominant phyla in herbivorous Ensifera. Contrarily, Cyanobacteria were found in very low abundance in reared Henosepilachna vigintioctopunctata (Coleoptera) (Lü et al, 2019) and in wild and mass-reared…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies found that the taxa with complex feeding habits had a higher gut bacterial diversity than those with single feeding habits [ 25 , 27 ]. This was also the result of our previous study on the gut bacterial diversity of Ensifera [ 36 ]. However, in this comprehensive study on gut bacteria, eukaryotes, viruses, and archaea by shotgun metagenomic sequencing, it was found that, although the omnivorous Gry had the most significant number of reads and contigs, its microbial diversity was not the highest.…”
Section: Discussionsupporting
confidence: 86%
“…We found that feeding characteristics were the main factor affecting the structure of the gut bacterial communities. The gut bacterial communities’ structure in Ensifera, from different taxa but with the same feeding habit, was similar [ 36 ]. Therefore, we selected three Ensifera species (Mec, Oce, and Gry) with high bacterial community diversity and minor intraspecific differences from the above samples to explore the similarities and differences in the gut microbiota’s composition and function mediated by feeding characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations